El emprendimiento y el crecimiento económico de las familias campesinas del cantón Chambo, provincia de Chimborazo. - Casigña Guzñay, Erika Alexandra (2024)
ABSTRACT: This research analyzes entrepreneurship's impact on the economic growth of the Chambo Canton, Chimborazo Province. It identifies challenges and opportunities to improve entrepreneurship in peasant families with the aim of promoting economic and social development in the region. The research question is raised about how entrepreneurship influences the economic growth of peasant families in the Chambo Canton. Entrepreneurs play a fundamental role in economic growth, as they generate employment, increase the production of goods and services, and help to reduce poverty. In this research, the hypothetical-deductive method will be used to study how entrepreneurship affects the economic growth of peasant families in the Chambo Canton. Surveys will be carried out on 212 peasant families, and a binary logistic regression econometric model will be used to analyze the collected data. On the other hand, the principal results showed regular operational efficiency thanks to the applied field research, with decreased productivity in recent years. Although they have increased investment in their businesses, the availability of technology remains moderate. Most depend on a single source of income and operate in sectors such as agriculture, brick manufacturing, and tourism. Despite considering that startups have contributed to economic growth, areas of improvement in innovation and scalability are identified.